Study of Physicochemical Parameters of Groundwater Quality of Kopargaon Area, Maharastra State, India duringPre-monsoon and Post-monsoon Seasons - Sunita R. Dandwate (E-Journal of Chemistry)
The physicochemical parameters were studied for water samples collected from different locations in Kopargaon area; It is one of the important taluka of Ahmednagar district, Maharastra state, India. The main purpose of the study was to ascertain the quality of water for drinking from selected locations. Assessment of water quality was done by comparing the parameters with standard values prescribed by different agencies. Most of the parameters were found within permissible limits of above standards. Correlation co-efficient ‘r’ was calculated for these parameters.